Inventory management - Control and replenishment / Imee Juiana Hj. Tajuddin - Imee Juiana, Hj Tajuddin (1999)
Planning and controlling as well as replenishments of inventories are crucial decisions. There are unpredicted situations which, lead firms to make decisions so that overstock or stock-outs would not occur. Keeping inventories will costs the firms money. An effective planning and control of inventories is fundamental if distributors are to achieve their goals simultaneously. Selecting of inventory ordering policy is crucial to guide planners and purchasers to determining what items to be ordered, when orders should be released and the order quantity.